Information-Seeking in Education for Creative Solving of Design and Engineering Problems - Slătineanu, Laurențiu; Coteață, Margareta; Hrițuc, Adelina; Beșliu-Băncescu, Irina; Dodun, Oana (Designs, 2023)
The paper aims to highlight the significance and place of information-seeking in finding improved solutions in the design of innovative products. The observation method was used to identify a way to increase the efficiency of searching for information needed when pursuing a creative solution to a design problem. The study was based on the experience gained in professional activities in higher education for industrial engineering and in the classes held for two academic subjects, when students’ creativity was stimulated, including in the search for information. One conclusion is that an experienced designer or researcher should make sketches and notes immediately after formulating the design objective. In this way, the possible inhibitory influence exerted by the results of a deep search for information could be avoided. In the case of a novice designer, it may be necessary to have a minimum collection of general information in the design topic field to familiarize the designer more with the problem addressed. The novice designer could thus develop a few sketches and notes and then go through a deeper stage of information-seeking. Another conclusion was that a certain minimum amount of scientific and technical knowledge is necessary to use technical creativity effectively.